(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Susandarini R, Khasanah U, Rosalia N. 2021. Ethnobotanical study of plants used as food and for maternal health care by the Malays communities in Kampar Kiri Hulu, Riau, Indonesia. Biodiversitas 22: 3111-3120. Studies to reveal the diversity of food plants on communities living in remote areas with limited access to the market are important as an effort in documenting the traditional knowledge. The same applies to the diversity of medicinal plants used in maternal health care for communities that have limited access to public health facilities. The documentation of ethnobotanical knowledge is not only for the purpose of developing the potential of these plants, but also could have an impact on their conservation in nature. This study aims to document the traditional knowledge on the diversity of food plants and medicinal plants used in maternal health care by Malays tribes living within the Bukit Rimbang Bukit Baling Wildlife Reserve, Kampar Kiri Hulu Subdistrict, Kampar District, Riau Province, Indonesia. The research was conducted in three villages by collecting data through interviews and followed by fieldwork to collect plant specimens for identification. Data on food plant diversity data were obtained from 20 informants, while data on the diversity and use of medicinal plants for maternal health care were obtained from 73 informants. The results showed that there were 76 species of food plants from 35 families. These food plants were used as secondary food ingredients, vegetables, fruit and spices with most of these plants were obtained from the yard of the house. Plants used for maternal health care identified from this study were 34 species from 26 families. These plants were used for various purposes during pregnancy, child delivery, postpartum recovery, and infant health care. The diversity of food plants and medicinal plants for maternal health care documented in this study showed the valuable role of plant resources in supporting daily needs and health care of the communities living in the fringe of forest area.